2021
DOI: 10.1007/jhep07(2021)035
|View full text |Cite
|
Sign up to set email alerts
|

The multiple-charm hierarchy in the statistical hadronization model

Abstract: In relativistic nuclear collisions the production of hadrons with light (u,d,s) quarks is quantitatively described in the framework of the Statistical Hadronization Model (SHM). Charm quarks are dominantly produced in initial hard collisions but interact strongly in the hot fireball and thermalize. Therefore charmed hadrons can be incorporated into the SHM by treating charm quarks as ‘impurities’ with thermal distributions, while the total charm content of the fireball is fixed by the measured open charm cross… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 66 publications
2
72
0
Order By: Relevance
“…A clear suppression of the production yield for p T > 3 GeV/c is visible in Pb-Pb collisions and it is stronger in central than in semicentral collisions. (SHMc) [66,67] (right panels of figure 5), which predicts the p T spectra of charm hadrons with a core-corona approach. The low-p T region is dominated by the core contribution described with a blast-wave function, while the corona contribution is more relevant at high p T and is parametrised from pp measurements.…”
Section: Transverse-momentum-differential Yieldsmentioning
confidence: 98%
See 1 more Smart Citation
“…A clear suppression of the production yield for p T > 3 GeV/c is visible in Pb-Pb collisions and it is stronger in central than in semicentral collisions. (SHMc) [66,67] (right panels of figure 5), which predicts the p T spectra of charm hadrons with a core-corona approach. The low-p T region is dominated by the core contribution described with a blast-wave function, while the corona contribution is more relevant at high p T and is parametrised from pp measurements.…”
Section: Transverse-momentum-differential Yieldsmentioning
confidence: 98%
“…The production yield of prompt D mesons per unit of rapidity, dN/dy, was obtained by extrapolating (where needed) the visible cross section to the full p T range. Since the p Tdifferential yields of D 0 mesons in the 0-10% and 30-50% centrality classes were measured JHEP01(2022)174 The right panels show the ratios in central Pb-Pb collisions compared to the predictions from the statistical hadronisation model (SHMc) [66,67] with a core-corona approach and the FastReso package [68] for resonance decays. Statistical (bars) and systematic (boxes) uncertainties are shown.…”
Section: Transverse-momentum-differential Yieldsmentioning
confidence: 99%
“…New results from the above mentioned statistical hadronization model, including an extension to include charm degrees of freedom were also presented [42]. It was shown that the measured multiplicities of single charm hadrons in heavy ion collisions at LHC energies can be well described with the same thermal parameters as for the light quark flavor hadrons.…”
Section: Hadronizationmentioning
confidence: 99%
“…Production probabilities for doubly-and triply-charmed hadrons are predicted to exhibit a characteristic enhancement hierarchy. The model also allows to determine transverse momentum spectra by combining it with blast wave models [42,43].…”
Section: Hadronizationmentioning
confidence: 99%
“…This ratio is larger than the one measured in pp collisions in the interval 4 < p T < 8 GeV/c. Figure 5 shows the p T -differential Λ + c /D 0 yield ratio measured in central collisions compared to three different theoretical predictions: Catania [21], TAMU [22], and the GSI/Hd+BW statistical hadronisation model [23]. Theoretical calculations that model the charm-quark transport in the QGP and include hadronisation via both coalescence and fragmentation processes describe the data.…”
Section: Charm and Beauty Production In Heavy-ion Collisionsmentioning
confidence: 99%